2014
DOI: 10.3329/bjvm.v12i2.21290
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Protozoan Diseases in Pet Dogs at District Veterinary Hospital, Sirajganj, Bangladesh

Abstract: A study was conducted to investigate the prevalence of protozoan diseases of 272 sick pet dogs submitted to the District Veterinary Hospital (DVH), Sirajganj during the two years period from January, 2009 to December, 2010. A total 7 types of protozoan diseases were identified in only 61 dogs and their variation in prevalence were analyzed on the basis of age and sex. The overall prevalence of protozoan diseases of pet dogs in the study area was observed 22.42%.The highest prevalence (%) of the diseases was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
5
4
Order By: Relevance
“…In different parts of the world the prevalence rate was higher than the present study as: Cuba 44.3% (Puebla et al, 2015); Nepal 46.7% (Satyal et al, 2013); Kandy district 90% (Perera et al, 2013). The prevalence documented in Mexico 26.5% (Chable et al, 2015; Bangladesh 22.4% (Mahmud et al, 2014;Iran 19.1% (Kohansal et al, 2017) was lower than all other studies conducted. Helminths reported in this study may be transmittable through the consumption of uncooked vegetables irrigated by water polluted by human feces and/or ingestion of faecally contaminated soil (Adanir and Tascl, 2013).…”
Section: Discussioncontrasting
confidence: 59%
“…In different parts of the world the prevalence rate was higher than the present study as: Cuba 44.3% (Puebla et al, 2015); Nepal 46.7% (Satyal et al, 2013); Kandy district 90% (Perera et al, 2013). The prevalence documented in Mexico 26.5% (Chable et al, 2015; Bangladesh 22.4% (Mahmud et al, 2014;Iran 19.1% (Kohansal et al, 2017) was lower than all other studies conducted. Helminths reported in this study may be transmittable through the consumption of uncooked vegetables irrigated by water polluted by human feces and/or ingestion of faecally contaminated soil (Adanir and Tascl, 2013).…”
Section: Discussioncontrasting
confidence: 59%
“…This is relatively high level of infection; and comparable to the report of Adejinmi and Osayomi (2010). This finding is higher than the reports from various areas: Martinez-Moreno et al 2007, Gingrich et al (2010), Mahmud et al (2014) and Mirzaei (2010) who reported 12.11%, 13.4%, 21.7% and13.26% from Spain, Galapagos Islands of Ecuador, Bangladesh and Iran, respectively. Such differences in the prevalence of enteric protozoa could be due to variation in geographic location, owners' awareness and the number of stray dogs' population in an area.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been reported that ectoparasitic infestation (tick infestation 11.88%, flea infestation 9.84% and mange 3.76%) cases were highest among the all reported clinical diseases in pet dog (Tarafder and Samad, 2010). Mahmud et al (2014) reported overall prevalence of protozoan diseases was 22.42% at Sirajganj, Bangladesh. So, this study was undertaken with the following objectives: to determine the overall prevalence of clinical diseases and conditions of pet animals at SAQVH, CVASU, Chittagong, Bangladesh; to know the prevalence of diseases and conditions in relation to age, sex, breed, affected systems of the body and etiology of pet animal's diseases (dog, cat and rabbit).…”
mentioning
confidence: 99%
“…The prevalence of infectious diseases and conditions of domestic animals and birds has already been performed in various regions of Bangladesh (Tarafder and Samad, 2010;Mahmud et al, 2014). But very few studies have been reported on the prevalence of clinical diseases and conditions in pet animals ( (Parvez et al, 2014).…”
mentioning
confidence: 99%